Issues on Regulation of Medical Services Contract in the Context of Healthcare Reform in Russia - ABESALASHVILI, Marine Zaurovna; ERTEL, Lyudmila Aleksandrovna; MUSTAFIN, Rafael Filevich; TKHAKUSHINOV, Rustem Askarbaevich (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
The submitted article covers some issues of regulations of contractual medical services in the Russian Federation. The contemporary state of regulations in connection with contractual medical services providing, as opined by many researchers, leaves much to be desired. Medical services contract, being a particular case of fee-based services contract has its specifics which must be reflected in regulations. The authors study the issues on setting the terms of services quality in the contract, quality and result relation in the context of healthcare system reform tasks, one of which is medical services quality improvement. In a medical services contract the quality of medical services is related by authors to their standards. Conclusions and offers on improvement of legal regulation are based on the study of issue’s background, current legal regulation, opinions of other researchers on commercial medicine. The result guarantee prohibition offered by authors in medical services contract, more detailed specification of terms and conditions, information mandatory for submission to patients will allow to protect consumer’s rights and decrease abuse in commercial medicine.
Keywords: service; contract; consumer; patient; medical assistance